2013
DOI: 10.1080/15226514.2012.702807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cadmium on Enzymatic and Non-Enzymatic Antioxidative Defences of Rice (Oryza SativaL.)

Abstract: The effects of 60-d cadmium (Cd) exposure on enzymatic and non-enzymatic antioxidative system of Oryza sativa L. seedlings at tillering stage were studied using soil culture experiment. Research findings showed that chlorophyll content of Oryza sativa L. declined with the increase in soil metal concentration. Cd pollution induced the antioxidant stress by inducing O2(-1) and H2O2, which increased in plants; at the same time, MDA as the final product of peroxidation of membrane lipids, accumulated in plant. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 15 publications
2
20
0
1
Order By: Relevance
“…CAT and POD are the most important enzymes in the regulation of intracellular H 2 O 2 levels (Blokhina et al, 2003). Some researchers have indicated the activity of antioxidative enzymes to be elevated in plant tissues under Cd stress (Elobeid et al, 2012;He et al, 2013a;Yu et al, 2013). However, here, the activity of antioxidant enzymes (SOD, CAT, and POD) was inhibited or unchanged after various Cd treatments (Fig.…”
Section: Antioxidant Enzymesmentioning
confidence: 46%
“…CAT and POD are the most important enzymes in the regulation of intracellular H 2 O 2 levels (Blokhina et al, 2003). Some researchers have indicated the activity of antioxidative enzymes to be elevated in plant tissues under Cd stress (Elobeid et al, 2012;He et al, 2013a;Yu et al, 2013). However, here, the activity of antioxidant enzymes (SOD, CAT, and POD) was inhibited or unchanged after various Cd treatments (Fig.…”
Section: Antioxidant Enzymesmentioning
confidence: 46%
“…Some kinase genes were also overexpressed in seedlings grown with As 2 O 3 45x, suggesting the importance of those signal proteins in response to environmental stimuli. Literature reports suggested that the oxidative tissue damage induced by heavy metals [ 58 , 59 ] could result also in the elevation of Ca 2+ concentration in plant cells, in which Ca 2+ played an important role in free radical scavenger induction [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reports have shown reduction in rice growth and biomass, which might possibly be as a result of different Cd-mediated toxicity mechanisms in rice [10]. Various other studies have also reported that the toxic effects of Cd increased rice seedlings oxidative stress by releasing reactive oxygen species (ROS) like malondialdehyde (MDA) contents, hydrogen peroxide (H 2 O 2 ), and electrolyte leakage which affects rice growth and performance [10,11]. Cadmium toxicity also altered leaf and root ultrastructure and caused structural damage to photosynthetic apparatus of rice [12].…”
Section: Introductionmentioning
confidence: 99%